STUDY OF THE EFFECT OF LOADING ON ANDESITE ROCK STRENGTH PARAMETERS - TONY (NIM : 12113020), DESTIAN
Rock conditions will affect the physical and mechanical properties of the rock. If rock conditions have changed from the initial conditions then the rock strength parameters will change as well. For example, when given loading, the loaded rocks have different strength parameters with the same rocks that are not loaded. Uniaxial compressive strength test, ultrasonic test, and triaxial test were performed on Andesite rock samples at initial condition without loading and samples at condition after loading. The results of laboratory tests will produce data such as uniaxial compressive strength, stress-strain curves, Young Modulus, Poisson Ratio, ultrasonic velocity, cohesion, and internal friction angle of rock samples. The results are then compared between the rocks in the initial conditions and the rocks that have been given loading. The results obtained are several parameters of rock strength decreased after loading. Changes in rock strength parameters will be higher along with the increased loading given to the rock.